Dual-Function Au@Y2O3:Eu3+ Smart Film for Enhanced Power Conversion Efficiency and Long-Term Stability of Perovskite Solar Cells - Chang Woo Kim (Nature Portfolio, 2017)
Abstract In the present study, a dual-functional smart film combining the effects of wavelength conversion and amplification of the converted wave by the localized surface plasmon resonance has been investigated for a perovskite solar cell. This dual-functional film, composed of Au nanoparticles coated on the surface of Y2O3:Eu3+ phosphor (Au@Y2O3:Eu3+) nanoparticle monolayer, enhances the solar energy conversion efficiency to electrical energy and long-term stability of photovoltaic cells. Coupling between the Y2O3:Eu3+ phosphor monolayer and ultraviolet solar light induces the latter to be converted into visible light with a quantum yield above 80%. Concurrently, the Au nanoparticle monolayer on the phosphor nanoparticle monolayer amplifies the converted visible light by up to 170%. This synergy leads to an increased solar light energy conversion efficiency of perovskite solar cells. Simultaneously, the dual-function film suppresses the photodegradation of perovskite by UV light, resulting in long-term stability. Introducing the hybrid smart Au@Y2O3:Eu3+ film in perovskite solar cells increases their overall solar-to-electrical energy conversion efficiency to 16.1% and enhances long-term stability, as compared to the value of 15.2% for standard perovskite solar cells. The synergism between the wavelength conversion effect of the phosphor nanoparticle monolayer and the wave amplification by the localized surface plasmon resonance of the Au nanoparticle monolayer in a perovskite solar cell is comparatively investigated, providing a viable strategy of broadening the solar spectrum utilization.